Efficacy of voxel-based dosimetry map for predicting response to trans-arterial radioembolization therapy for hepatocellular carcinoma: a pilot study. Issue 12 (12th August 2021) - Yoo, Min Young; Paeng, Jin Chul; Kim, Hyo-Cheol; Lee, Min Sun; Lee, Jae Sung; Lee, Dong Soo; Kang, Keon Wook; Cheon, Gi Jeong
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Typical clinical dosimetry models for trans-arterial radioembolization (TARE) assume uniform dose distribution in each tissue compartment. We performed simple voxel-based dosimetry using post-treatment 90 Y PET following TARE with 90 Y-resin microspheres and investigated its prognostic value in a pilot cohort. Method: Ten patients with 14 hepatocellular carcinoma lesions who underwent TARE with 90 Y-resin microspheres were retrospectively included. The partition model-based expected target tumor dose (TDp) was calculated using a pretreatment 99m Tc-macroaggregated albumin scan. From post-treatment 90 Y-microsphere PET and voxel-wise S-value kernels, voxel-based dose maps were produced and the absorbed dose of each lesion (TDv) was calculated. Heterogeneity of intratumoral absorbed doses was assessed using the SD and coefficient of variation of voxel doses. The response of each lesion was determined based on contrast-enhanced MRI or CT, or both. Lesion responses were classified as local control success or failure. Prognostic values of dosimetry parameters and clinicopathological factors were evaluated in terms of progression-free survival (PFS) of each lesion. Results: TDv was significantly different between local control success and failure groups, whereas tumor size, TDp and intratumoral dose heterogeneity were not. Univariate survival analysis identified serum aspartate transaminase level ≥40 IU/L, tumor size ≥66 mm and TDv <81 Gy as significant prognostic factors for PFS. However, only TDv was an independent predictive factor in the multivariate analysis ( P = 0.022). There was a significant correlation between TDv and PFS ( P = 0.009; r = 0.669). Conclusions: In TARE, voxel-based dose index TDv can be estimated on post-treatment 90 Y PET using a simple method. TDv was a more effective prognostic factor for TARE than TDp and clinicopathologic factors in this pilot study. Further studies are warranted on the role of voxel-based dose and dose distribution in TARE.